ELNAIS meets EASIN: distribution of marine alien species in Greece using EASIN mapping services and ELNAIS spatial data - KATSANEVAKIS, S.; ZENETOS, A.; POURSANIDIS, D.; NUNES, A.L.; DERIU, I.; BOGUCARSKIS, K.; CARDOSO, A.C. (Mediterranean Marine Science, 2013)
The European Alien Species Information Network (EASIN) was created with the aim to provide easy access to accurate information on alien species in Europe. EASIN allows the retrieval of spatial information from existing online data providers in order to produce integrated georeferenced distribution maps of alien species in Europe. In November 2012, a new data provider, the Ellenic Network on Aquatic Invasive Species (ELNAIS), joined EASIN; this has significantly increased the available georeferenced information on marine/estuarine alien species in Greek waters. Here, we use maps created by EASIN to show differences in patterns of distribution in Greece for the most abundant Phyla of marine alien species - Mollusca, Arthropoda, Chordata and Annelida. We also show that the two main pathways of introduction of marine alien species (Lessepsian migration and Shipping) are related to different patterns of species spatial distribution in Greece. Overall, the tools provided by EASIN can greatly aid scientists and policy makers in obtaining high quality information on marine alien species in Greece, especially after the association with ELNAIS.